Manajemen Strategi Pengkaderan Pelajar Islam Indonesia (PII) dalam meningkatkan jumlah anggota dikota Palembang - Efendi, Agus Awal; Suryati, Suryati; Walian, Anang (CV. ITTC INDONESIA, 2022)
This research is entitled (Management Strategy for Recruiting Indonesian Islamic Students (PII) in increasing the number of members in the city of Palembang which aims to find out what the strategy is carried out by the management in recruiting members. In addition, it will also explain how the obstacles or obstacles faced by the administrators in increasing and retain members. Cadres have an important role in the organization to develop the organization. In addition, cadres / administrators must also work on how to establish good relations with government agencies. The PII Palembang City organization plays an important role in the formation of the Islamic character of students in Palembang City, Introduction The organization of PII is through socialization/counseling to schools in Palembang.The research method used is a qualitative research approach with data collection techniques namely through interviews, observation, and documentation.As for data analysis using descriptive. The conclusion is that the Strategic Management used by the management of the PII Palembang City organization is Pre-Batra Indonesian Islamic Students, Cadre Follow Up Activities and approaches taken between organizational management and prospective members.